2019
DOI: 10.1093/intqhc/mzz047
|View full text |Cite
|
Sign up to set email alerts
|

Access of patients with breast and lung cancer to chemotherapy treatment in public and private hospitals in the city of Buenos Aires

Abstract: Objectives Describe the time elapsed from the diagnosis to treatment with chemotherapy for patients with breast and lung cancer at public and private hospitals in Buenos Aires. Design Retrospective cohort study. Setting Three public and three private academic hospitals in Buenos Aires. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A common theme was the private sector performing better on process quality for resource-intensive interventions such as those requiring more health worker time, specialised expertise, costly medications, or diagnostics. Such examples included thrombolysis for stroke patients, [ 70 ] interventions for acute coronary syndrome (ACS), post-ACS management, [ 76 , 113 , 114 ] and cancer treatment, [ 69 , 107 , 115 , 116 ] and routine screening for diabetes complications [ 117 ]. Two studies also reported that patients in the private sector had access to new or expensive medications for cancer treatment [ 118 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A common theme was the private sector performing better on process quality for resource-intensive interventions such as those requiring more health worker time, specialised expertise, costly medications, or diagnostics. Such examples included thrombolysis for stroke patients, [ 70 ] interventions for acute coronary syndrome (ACS), post-ACS management, [ 76 , 113 , 114 ] and cancer treatment, [ 69 , 107 , 115 , 116 ] and routine screening for diabetes complications [ 117 ]. Two studies also reported that patients in the private sector had access to new or expensive medications for cancer treatment [ 118 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies also reported that patients in the private sector had access to new or expensive medications for cancer treatment [ 118 , 119 ]. When it came to less complex and less resource intensive interventions, a number of studies [ 68 , 69 , 111 ] found that public sector facilities were able to perform as well or better than the private sector.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment receipt was reported for different types of SACT which included chemotherapy, immunotherapy, targeted therapy which included cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i), unspecified SACT and endocrine therapy. Seven studies reported chemotherapy where overall receipt ranged from 22 to 60% [ 29 , 30 , 35 , 37 , 38 , 41 , 43 ]. Receipt of endocrine therapy was reported in one study which evaluated factors associated with treatment receipt among women with hormone receptor-positive disease where overall treatment receipt was reported as 70.8% [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported time to treatment [ 34 , 39 – 41 ]. These included two studies which reported time to treatment with non-specified SACT chemotherapy and immunotherapy [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation